Transferring knowledge on halal awareness amongst Orang Asli community - Othman, Khadijah; Jamaludin, Mohammad Aizat (Yamani Angle Sdn Bhd, 2021)
The Halal industry has been widely established in Malaysia and leading to achieve the global hub promotion throughout the world. Due to that, the ministry of education needs an extra effort as to gain the awareness among Orang Asli community by helping them in terms of education. This kind of effort can be helping in sustaining and flourishing in the Halal industry. In order to develop the idea, the action must be taken in the early ages as to make sure the knowledge will be spread evenly and nurturing the understanding wholesomeness concept of Halal. By achieving the idea, the parental awareness, Halal exposure, language, customs and traditions and also religious belief on Halal education need to apply among them.